Intra-tumoural microenvironment and bugs-based drug design: foreseeable future in oncology and immuno-oncology - Kaźmierczak-Siedlecka, Karolina; Kucharski, Robert; Stachowska, Ewa; Pelikant-Małecka, Iwona; Marano, Luigi; Makarewicz, Wojciech; Kalinowska, Magdalena; Dambrauskas, Žilvinas; Kalinowski, Leszek (Frontiers in Pharmacology, 2026)
The term tumour microenvironment (TME) encompasses the coexistence of microorganisms and different cellular elements including endothelial cells, macrophages, cancer-associated fibroblasts and a complex network of microvessels. Integration of tumour immunity and intratumoural microbiome into anti-cancer strategies represents a promising frontier in precision oncology (for instance in case of solid cancers, such as pancreatic or colorectal tumours). Characterization of the intratumoural microbial signature has emerged as a critical step in drug discovery, influencing therapeutic efficacy as well as resistance. There are several approaches, such as elimination of pathogenic microorganisms within the TME, modulation of specific microbial–immune axes, including interactions among microbial species that may enhance or suppress tumour progression, and exploitation of bacterial strains engineered to express pro-drug-converting enzymes for localized tumour therapy via intratumoural injection. Furthermore, tumour organoid–immune co-culture models, particularly when combined with 3D bioprinting technologies, offer robust experimental platforms for dissecting tumour–microbiome–immune crosstalk. The reciprocal communication between the immune system and the tumour-associated microbiome/metabolome highlights novel opportunities for therapeutic innovation in oncology and immuno-oncology.